2016
DOI: 10.3389/fimmu.2016.00113
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Myeloid Regulatory Cells

Abstract: Myeloid cells are critically involved in the pathophysiology of cancers. In the tumor microenvironment (TME), they comprise tumor-associated macrophages (TAMs), neutrophils (TANs), dendritic cells, and myeloid-derived suppressor cells, which are further subdivided into a monocytic subset and a granulocytic subset. Some of these myeloid cells, in particular TAMs and TANs, are divided into type 1 or type 2 cells, according to the paradigm of T helper type 1 or type 2 cells. Type 1-activated cells are generally c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 116 publications
0
50
0
Order By: Relevance
“…Immunomodulatory therapy for CAD may therefore not only target the inflammatory propensity of macrophages, but may also improve their protective functions as antigen-presenting cells. Combined pro-and anti-immune functions is exemplified in tumor-associated macrophages and related myeloid cell populations (68). Unleashing antitumor T cells by directly blocking negative signaling with anti-PD-1 or anti-PD-L1 antibodies has caused a paradigm shift in cancer immunotherapy.…”
Section: Pd-l1mentioning
confidence: 99%
“…Immunomodulatory therapy for CAD may therefore not only target the inflammatory propensity of macrophages, but may also improve their protective functions as antigen-presenting cells. Combined pro-and anti-immune functions is exemplified in tumor-associated macrophages and related myeloid cell populations (68). Unleashing antitumor T cells by directly blocking negative signaling with anti-PD-1 or anti-PD-L1 antibodies has caused a paradigm shift in cancer immunotherapy.…”
Section: Pd-l1mentioning
confidence: 99%
“…Similar to TAMs, TANs are more likely to be polarized to the N2 type in the tumor microenvironment [23]. Many reports have indicated that TANs cause therapeutic resistance of cancers through secretion of proteins.…”
Section: Therapeutic Resistance Regulated By Myeloid Cellsmentioning
confidence: 99%
“…Macrophages, like fibroblasts, can be activated in the presence of tumor cells to form tumor associated macrophages (TAMs)(reviewed in 375,376 ). TAMs can promote tumor growth and angiogenesis by secreting growth factors such as EGF and VEGF 376378 , and by releasing anti- inflammatory cytokines, such as IL10 and TGFβ 376 .…”
Section: Immune Interactionsmentioning
confidence: 99%
“…In NK cells, inflammatory cytokines like IL12 and IL18 can inhibit TGFαR-II and SMAD expression 401 . TGFβ also promotes TAM differentiation 74,94,375 .…”
Section: Immune Interactionsmentioning
confidence: 99%